2015
DOI: 10.1111/edt.12185
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of weakened bovine teeth after long‐term use of calcium hydroxide

Abstract: Apexification with periodic changes of calcium hydroxide medicament leads to weakness of the teeth independent of the irrigation solution used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
(42 reference statements)
1
21
0
5
Order By: Relevance
“…Calcium hydroxide is the most commonly used root canal dressing for late replantation, and it is considered to be the medication of choice due to its alkaline pH and bactericidal effects, which may slow or limit inflammatory and replacement resorption . To observe these effects, a long application time with successive changes is required, which has been associated with a detrimental effect on the fracture resistance of root dentin . Additionally, as observed in this research, studies in animal models have demonstrated that calcium hydroxide is ineffective in preventing inflammatory and replacement resorption following tooth replantation .…”
Section: Discussionmentioning
confidence: 79%
“…Calcium hydroxide is the most commonly used root canal dressing for late replantation, and it is considered to be the medication of choice due to its alkaline pH and bactericidal effects, which may slow or limit inflammatory and replacement resorption . To observe these effects, a long application time with successive changes is required, which has been associated with a detrimental effect on the fracture resistance of root dentin . Additionally, as observed in this research, studies in animal models have demonstrated that calcium hydroxide is ineffective in preventing inflammatory and replacement resorption following tooth replantation .…”
Section: Discussionmentioning
confidence: 79%
“…There is limited number of studies in the literature about the effects of CHX on the fracture strength of teeth. In the Valera et al study [28], irrigation with 2% CHX showed a significantly lower fracture resistance than that of the control group. As an intracanal medicament, 0.5% CHX was added to CH in Prabhakar et al's study [29], and the mixture was applied to the root canal for 30 days.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, many studies have used them for laboratory investigations, including studies on root and crown fractures. [17][18][19] To reduce variations, factors, such as root length and root dentin thickness were standardized to 20 and 2.5 mm respectively, similar to the 2012 study by Alsamadani et al 20 Some authors have employed impression materials to simulate the periodontal ligament. 18,21 The periodontium effect was not reproduced in this study, and all roots were embedded directly in PVC cylinders with acrylic resin, 2 mm below the cementoenamel junction.…”
Section: Discussionmentioning
confidence: 99%